The Impact of the Financial Reporting of Liabilities and Assets of Deferred Income Tax in the quality of Accounting Information - علي سلامة ابراهيم; محمد صلاح هادي (Journal of Economics and Administrative Sciences, 2016)
Abstract The research problem Focused about extent adoption of the financial reporting obligations and assets of the deferred income tax attributable to the concepts of accounting theory and whether the tax laws or accounting principles as well as local accounting rules to recognize the obligations and assets of deferred income tax in the financial statements, and what is the impact of the financial reporting of liabilities and assets Deferred tax in the quality of accounting information, and research aims to the statement of the accounting concepts of the theory of financial reporting obligations and assets of deferred income tax, view and analyze the differences in reporting, resulting from a discrepancy in the accounting treatments in accordance with the accounting principles and the requirements of the tax laws and accounting rules in the local environment and compare these rules with the international financial reporting standard IAS (12), as well as a measure of financial reporting obligations and assets of deferred income tax in the quality of information effect accounting by identifying qualitative characteristics of accounting information. The study concluded There is the impact of the financial reporting of liabilities and assets of deferred income tax in the quality of accounting information, which showed the results of a test research hypotheses, and presented research a number of recommendations were the most important of the need for financial reporting obligations and assets of deferred income tax in the financial statements of corporation as they have a positive impact on economic decisions investors, creditors and other interested parties to submit accounting information being characterized by high quality in terms of relevance for those decisions and certified of their representation of events related.